Justification of the Subject of Cognition Problem in Modern Social and Legal Sciences Methodology - Дудченко, Валентина Віталіївна; Дудченко, В. В.; Дудченко, Валентина Витальевна; Dudchenko, Valentyna V.; Dudchenko, Valentina V.; Цуркан-Сайфуліна, Юлія Василівна; Цуркан-Сайфуліна, Ю. В.; Цуркан-Сайфулина, Юлия Васильевна; Tsurkan-Saifulina, Yuliia V.; Вітман, Костянтин Миколайович; Вітман, К. М.; Витман, Константин Николаевич; et al. (ASERS Publishing, 2018)
The article is devoted to the study of the essential characteristics of the subject of cognition. The process of cognition, being one of the oldest issues in the history of humankind, has always been and remains highly relevant today. This is due to the irrepressible desire of a person to know the world around her/him and herself/himself. If the study of the surrounding world is basically the prerogative of the natural sciences, then self-cognition is the object of study in the humanities. The process of cognitive activity is considered by a number of the humanities and social sciences: philosophy (in a generalized sense), history, psychology, pedagogy, sociology, etc., but it begins to occupy a separate place in the philosophy of law. Modern human needs to know the measure, opportunity, freedom and responsibility of the process of cognition. In the article, from the point of view of critical realism, the current state of the methodology of cognition is analyzed and the necessary tendencies in changing the worldview and defining the new methodology of the humanities are substantiated. The experience of the post-Soviet countries with dogmatic ideology and destructive methodology was used as an illustrative material. It has been established that only a free-thinking subject and a methodology developed on the principles of the supremacy of spiritual values can improve the reverent approach to the person and the world as a whole and come closer to the cognition of absolute truth.

Стаття присвячена дослідженню сутнісних характеристик суб’єкта пізнання. Процес пізнання, будучи однією з найдавніших проблем в історії людства, завжди був і залишається дуже актуальним сьогодні. Це пов’язано з нестримним бажанням людини пізнати навколишній світ і себе. Якщо вивчення навколишнього світу в основному є прерогативою природничих наук, то самопізнання є об’єктом вивчення гуманітарних наук. Процес пізнавальної діяльності розглядається рядом гуманітарних і суспільних наук: філософією (в узагальненому розумінні), історією, психологією, педагогікою, соціологією та ін., але він починає займати окреме місце у філософії права. Сучасній людині необхідно знати міру, можливості, свободу та відповідальність процесу пізнання. У статті з точки зору критичного реалізму проаналізовано сучасний стан методології пізнання та обґрунтовано необхідні тенденції зміни світогляду та визначення нової методології гуманітарних наук. Як ілюстративний матеріал використано досвід пострадянських країн з догматичною ідеологією та деструктивною методологією. Встановлено, що лише вільнодумний суб’єкт і методологія, розроблена на засадах верховенства духовних цінностей, можуть удосконалити трепетне ставлення до людини і світу в цілому, наблизитися до пізнання абсолютної істини.
Dudchenko V. V. Justification of the Subject of Cognition Problem in Modern Social and Legal Sciences Methodology / V. V. Dudchenko, Yu. V. Tsurkan-Saifulina, K. M. Vitman // Journal of Advanced Research in Law and Economics. - V. 9. - N. 7(37). - ASERS Publishing, 2018. - P. 2296-2308.
Keywords: subject of cognition; cognitive activity; intellect; scientific methodology; dialectical materialism; legal philosophy; предмет пізнання; пізнавальна діяльність; інтелект; наукова методологія; діалектичний матеріалізм; філософія права; Research Subject Categories::SOCIAL SCIENCES::Social sciences